Pelatihan Aplikasi Quick Count sebagai Inovasi Kurikulum Merdeka dalam Kegiatan Proyek Penguatan Profil Pelajar Pancasila (P5) - Susanti, Nanik; Irawan, Yudie; Handayani, Putri Kurnia (Universitas Muria Kudus, 2025)
The Merdeka Curriculum is designed to provide flexibility for educators in creating quality learning experiences tailored to students' needs. One of its co-curricular programs is the Pancasila Student Profile Strengthening Project (P5), developed based on specific themes set by the government. P5 promotes flexible learning, collaboration, creativity, and active student participation in face-to-face activities. It encourages students to generate ideas and take real actions that impact themselves and their surroundings. At the high school level, there are seven P5 themes, while vocational schools have nine. SMA N 6 Semarang is among the schools implementing the Merdeka Curriculum and has carried out several P5 themes. In the 2023/2024 academic year, the school plans to apply the technology and engineering theme by developing a quick count application. However, challenges remain, such as the limited programming skills of students and teachers, as well as the small number of educators with expertise in information technology.Kurikulum Merdeka dirancang untuk memberikan fleksibilitas kepada pendidik dalam menciptakan pengalaman belajar yang berkualitas dan sesuai dengan kebutuhan siswa. Salah satu program dalam kurikulum ini adalah Projek Penguatan Profil Pelajar Pancasila (P5), yang dikembangkan berdasarkan tema-tema tertentu dari pemerintah. P5 mendorong pembelajaran yang fleksibel, kolaboratif, kreatif, serta meningkatkan partisipasi aktif siswa dalam kegiatan tatap muka. Melalui proyek ini, siswa diajak untuk menghasilkan ide dan aksi nyata yang berdampak bagi diri sendiri maupun lingkungan sekitar. Di tingkat SMA, terdapat tujuh tema P5, dan sembilan tema untuk SMK. SMA N 6 Semarang menjadi salah satu sekolah yang telah menerapkan Kurikulum Merdeka dan melaksanakan beberapa tema P5. Pada tahun ajaran 2023/2024, sekolah berencana menerapkan tema rekayasa dan teknologi melalui pengembangan aplikasi quick count. Tantangan yang dihadapi adalah keterbatasan kemampuan siswa dan guru dalam pemrograman serta jumlah pendidik IT yang masih sedikit.